Long-term Outcomes (10 years) of Hepatic Transplantation in a Patient with Hepatic Adenomatosis: A Case Report - Abdullah Almunifi (Journal of Pharmacy and Bioallied Sciences)
Hepatocellular adenoma is a rare benign liver neoplasm, and hepatic adenomatosis is associated with risks such as intertumoral hemorrhage or necrosis. The imaging features of adenomatosis closely resemble those of solitary adenomas, differing only in the number of lesions. This study reports a case of an 18-year-old woman with perturbed liver function enzymes and multiple hepatic nodules. She had no significant medical history, chronic liver disease, or diabetes and was not taking any regular medications or anabolic steroids. Abdominal ultrasound revealed hepatomegaly and multiple hepatic nodules. Subsequently, the patient underwent hepatic orthotropic transplantation without any complications and was followed-up for 10 years. Multiple lesions with suspicious or confirmed malignant transformation and unwillingness to undergo surgical resection are considered leading indications for hepatic transplantation. Despite efforts to manage the condition conservatively, including hepatic transplantation, the patient experienced complications related to immunosuppressant therapy and ultimately developed chronic rejection. Hepatic transplantation is rarely indicated for benign liver tumors, especially when life-threatening complications or hepatic tumor malignant transformation cannot be ruled out, and tumors are unrespectable. This case highlights the complexity of managing hepatic adenomatosis and underscores the importance of individualized treatment strategies and long-term follow-up.